Kompresi File Video Menggunakan Algoritma Punctured Elias Code - Rangkuti, Tondhita Syah Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Video files are large in size, especially if they are high quality and have an MP4 extension. The MP4 extension is a minimally compressed format. This poses a problem in the processing of video files and also requires a large amount of storage space. If a video file is large in size, it can affect the file transfer process. Therefore, the file transfer process has two possible outcomes: the video file may take a long time to transfer, or the transfer may fail due to the file size exceeding the maximum storage limit. This issue can be resolved by compressing the video file data. Data compression reduces the storage size of the file on both internal and external memory, thereby accelerating the transfer process as the file size becomes smaller. Data compression has several algorithms that can be used. In this study, the author uses the punctured Elias code algorithm, which is a lossless compression technique, so that the decompressed result of the compressed data is the same as the original data. The design of this system consists of two main processes: the compression process and the decompression process, as well as the process of calculating the performance metrics of the Compression Ratio (RC), Compression Ratio (CR), and Redundancy. In the compression process of a colored video file with the MP4 extension using the Additive Code algorithm, the Ratio of Compression (RC) was 1.52, the Compression Ratio (CR) was 65%, and the Redundancy was 34%. In this video file compression research using the punctured Elias code algorithm, it is hoped that it can help users compress large video files into smaller ones.